30(x + 2) - 6(x - 5) - 14x = 100
=> 30x + 60 - 6x + 30 - 14x = 100
=> 10x + 90 = 100
=> 10x = 100 - 90
=> 10x = 10
=> x = 10 : 10
=> x = 1
b ) Ta có : 30 . ( x + 2 ) - 6 . ( x - 5 ) - 14x = 100
Suy ra 30x + 30 . 2 - 6x - ( - 6 ) . 5 - 14x = 100
Suy ra 30x + 60 - 6x + 30 - 14x = 100
Suy ra 30x - 6x - 14x = 100 - 60 - 30
Suy ra 10x = 10
Vậy x = 1
30( x + 2 ) - 6( x - 5 ) - 14x = 100
=> 30x + 60 - 6x + 30 - 14x = 100
=> ( 30x - 6x - 14x ) + ( 60 + 30 ) = 100
=> 10x + 90 = 100
=> 10x = 100 - 90 = 10
=> x = 10 : 10 = 1
\(30\left(x+2\right)-6\left(x-5\right)-14x=100\)
\(\Rightarrow30x+60-6x+30-14x=100\)
\(\Rightarrow30x-6x-14x=100-30-60\)
\(\Rightarrow10x=10\)
\(\Rightarrow x=1\)
=> 30x+60-6x+30-14x=100
=> 10x+90=100
=> 10x=10
=> x=1
mấy câu này em chưa học nên chưa biết chị ạ em lớp 4 mà